Inovasi Digital dalam Manajemen Keamanan Sekolah: Studi Penggunaan Aplikasi “Ali Topan” untuk Mengatasi Perundungan - Abdul Majid (CENDEKIAWAN, 2025)
Bullying is a serious issue in the educational environment that affects students' safety and well-being. This study aims to analyze the implementation of school principal management in the actuating phase of the bullying reduction program using the "Ali Topan" application at SDN Sawah Besar 01 Semarang. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that the principal actively coordinates, motivates, and supervises the program by involving all school elements, including teachers, students, and parents. The implementation of the "Ali Topan" application has proven effective in raising students' awareness of bullying impacts, expediting reporting processes, and facilitating more responsive follow-up actions. The improvement in the education quality report score in the school safety climate element demonstrates the program’s success in creating a safer and more conducive school environment. This study provides recommendations for policymakers to enhance the effectiveness of digital-based bullying prevention programs in elementary schools.